An Explorative Study of Indonesian Traditional Cheese 'Dangke' as High Protein Food from Enrekang, South Sulawesi - Sa'pang, Mertien; Salam, Abdul; Harna, Harna; Rahmayanti R, Andi; Seprianto, Seprianto; Nurmalasari, Mieke; Ruhmayanti, Nur Ayu; Swamilaksita, Prita Dhyani (Poltekkes Kemenkes Palu, 2023)
This study aimed to examine the historical and cultural values of dangke as a traditional food, its potential as a source of animal protein, and the methods of its preparation and presentation. This qualitative descriptive study used in-depth interviews with key informants, focus group discussions with primary and supporting informants, and observation to collect data. The findings of this study indicate that dangke, which was originally made from buffalo milk and enriched with enzymes from papaya sap, reflects the culinary heritage of the Massenrempulu tribe in Enrekang Regency, South Sulawesi. However, the limited supply of buffalo milk has led to the modification of dangke using cow's milk in some parts of Enrekang. Historically, dangke has been served with rice or